Wakaf Uang Menurut Tuan Guru Nahdlatul Wathan di Lombok Nusa Tenggara Barat - Nugroho, Anton Priyo; Achiria, Siti; Muliadi, M. Arif (Fakultas Syariah IAIN Purwokerto, 2017)
Nahdlatul Wathan has a significant role in religious social development, especially in the Lombok area of West Nusa Tenggara (NTB). The role cannot be separated from the tuan guru as religious leaders of Nahdlatul Wathan. This is not to deny the other party's role, but the role of religious leader like tuan guru is very dominant in Lombok. On the other hand, cash waqf develops as one of the contemporary issues of the ummah. Cash waqf is still considered a new phenomenon among Muslims in Indonesia, so there are still differences of opinion between religious leaders. Tuan guru’s view on cash waqf is very important in order for cash waqfto develop well. Therefore this study aims to know the opinion of the tuan guru about cash waqf. This study used a qualitative approach, and it used interview method to 10 tuan gurus of Nahdhatul Wathan in Lombok NTB. The study found that most of tuan guru allowed the cash waqf with the consideration that the benefits were greater than the harm. Only a small proportion of tuan guruforbid cash waqf because waqf should be fixed, unchanged and should not be reduced.